Legal Liability Of Students Of The Medical Professional Education Program (Medicine Coas) For Alleged Medical Negligence At The Hospital - Widagdo, Rhido Hedriyanna; Arie Mangesti, Yovita (Journal Evidence Of Law, 2024)
Medicine Coas is a student of a medical professional education program in a hospital who is pursuing a doctor's degree (dr). This paper presents the findings of normative research conducted through a statue approach and conceptual approach. The conclusion that can be drawn is that the hospital has a legal obligation as stated in Article 193 of Law 17 of 2023 concerning Health, to take responsibility for medical negligence committed by students of the Medicine Coas program. This responsibility applies if the actions of Medicine Coas students are in accordance with the instructions given by the supervising doctor and can be proven through medical records. Medicine Coas program students do not have the authority to make decisions independently in taking medical action at the hospital, because they do not have the right to do so unless they have a license to practice such as doctors, nurses, midwives. Therefore, in taking an action related to a person's life, Medicine Coas students must seek the approval of the supervising doctor in accordance with hospital standards or regulations that apply in the hospital.